Traffic Modeling and Access Control for Machine Type Communications：A Comprehensive Survey - Xin Jian; Xiaoping Zeng (Dianxin kexue)
The historical development，traffic characteristics，potentials and challenges of machine type communications（MTC）were introduced.A comprehensive survey on the traffic modeling and access control for the concurrent data transmission from massive MTC devices was made.With the recommendations on traffic engineering suggested by International Telecommunication Union （ITU）and International Teletraffic Congress （ITC），some important issues and key problems in the fields of traffic characteristics analysis，traffic modeling and access control for MTC were summarized，in order to provide engineers and researchers insights on the improved performance analysis and enhanced access control for carrier network，which would promote the deployment and standardization of MTC and internet of things.